Obtaining Lignin from Nutshells under Mild Extraction Conditions and Its Use as a Biostimulant in Tomato Seedlings - José Alejandro Díaz-Elizondo; Azrrael Ayala-Velazco; Adalberto Benavides-Mendoza; Francisco Javier Enriquez-Medrano; Julia Medrano-Macías (Horticulturae)
Biostimulants are an important alternative to improve and promote higher efficiency in cropping systems. Although the biostimulant industry has been developing for several years, there are still areas of opportunity for new sources of biostimulants as well as new ecofriendly extraction techniques that allow for a circular economy and the reuse of waste. Lignin is a heteropolymer that constitutes about 40% of the plant cell wall. A great source of lignin is agrowastes, giving it added value. Recently, its use has been tested in agronomy as a carrier of nutrients and pesticides. Walnuts are produced on a large scale in Northern Mexico, and the shell represents between 15 and 40% of its total weight. However, to obtain this biopolymer, to date, non-environmentally friendly techniques have been used; for this reason, it is necessary to find extraction alternatives to make this proposal sustainable. In this work, the obtaining and characterization of lignin through mild extraction conditions from nutshells and its evaluation as a biostimulant on the growth of tomato seedlings are reported. Lignin was extracted by hydrolysis with a mixture of acetic acid and distilled water (65:35 v/v). The results showed that it was possible to obtain 15% (w/w) lignin using mild solvents, evidenced by thermogravimetric analysis (TGA), proton magnetic nuclear resonance (H-RMN), and infrared (IR). Subsequently, lignin solutions were prepared at different concentrations, 0, 10, 50, and 100 ppm, and applied via foliar weekly to tomato seedlings. A greater fresh weight of the stem was found with 10 and 50 ppm, and the height and the fresh biomass increased with the three concentrations (10, 50, and 100 ppm), concluding that lignin extracted from nutshells using mild conditions can act as a plant biostimulant.